2006
DOI: 10.1128/jb.188.3.909-918.2006
|View full text |Cite
|
Sign up to set email alerts
|

Function and Evolution of Plasmid-Borne Genes for Pyrimidine Biosynthesis inBorreliaspp

Abstract: The thyX gene for thymidylate synthase of the Lyme borreliosis (LB) agent Borrelia burgdorferi is located in a 54-kb linear plasmid. In the present study, we identified an orthologous thymidylate synthase gene in the relapsing fever (RF) agent Borrelia hermsii, located it in a 180-kb linear plasmid, and demonstrated its expression. The functions of the B. hermsii and B. burgdorferi thyX gene products were evaluated both in vivo, by complementation of a thymidylate synthase-deficient Escherichia coli mutant, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Only 5 to 10% of the deduced ORFs of the 3 large plasmids defined here had identifiable homologs to proteins from organisms outside the Borrelia genus (see Tables S2 and S3 in the supplemental material). These ORFs encode products involved with nucleotide biosynthesis (thyX, nrdE, nrdF, and nrdI) (38,50) and putative bacterial plasmid replication and partitioning (paralogous family 32 [PFam32], PFam49, PFam50, and PFam57) (16,43). The remaining protein sequences of ORFs were found to be homologous to proteins found in LD Borrelia species as well as in RF species.…”
Section: Sizes Of the Large Linear Plasmidsmentioning
confidence: 92%
See 2 more Smart Citations
“…Only 5 to 10% of the deduced ORFs of the 3 large plasmids defined here had identifiable homologs to proteins from organisms outside the Borrelia genus (see Tables S2 and S3 in the supplemental material). These ORFs encode products involved with nucleotide biosynthesis (thyX, nrdE, nrdF, and nrdI) (38,50) and putative bacterial plasmid replication and partitioning (paralogous family 32 [PFam32], PFam49, PFam50, and PFam57) (16,43). The remaining protein sequences of ORFs were found to be homologous to proteins found in LD Borrelia species as well as in RF species.…”
Section: Sizes Of the Large Linear Plasmidsmentioning
confidence: 92%
“…3B), the GC skew around the operons for outer surface proteins A and B (bba15 and bba16) and for decorin-binding proteins A and B (bba24 and bba25) is opposite to that of the surrounding sequence that is common to RF and LD species. This is an indication that these operons, which are unique to LD species, were likely acquired horizontally in the LD clade after the descent from an ancestral taxon, as appears to be the case for other operons (50,61).…”
Section: Sizes Of the Large Linear Plasmidsmentioning
confidence: 94%
See 1 more Smart Citation
“…Heterologous complementation tests have shown that E. coli thyA can be functionally replaced by thyX genes from a variety of sources (9,11,20,29). To investigate whether the reciprocal nonorthologous replacement is possible, we constructed transferable plasmids carrying either the R. sphaeroides thyA gene alone (pDL14) or the R. sphaeroides thyA and folA genes (pDL12) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous genetic studies on thyX either were performed using poorly defined genetic backgrounds (7) or were based upon multicopy heterologous complementation systems using either bacterial (9,12,20,29) or viral (10,11) thyX genes.…”
mentioning
confidence: 99%